AB0970 Utility of Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography for Early Diagnosis and Evaluation of Disease Activity of Relapsing Polychondritis. (10th June 2014) - Yamashita, H.; Kubota, K.; Takahashi, Y.; Kaneko, H.; Kano, T.; Mimori, A.
Abstract : Background: Relapsing polychondritis (RPC) is relatively rare, and early diagnosis is difficult. Objectives: We investigated the utility of FDG-PET/CT for the diagnoses of RPC and evaluation of disease activity. Methods: Five RPC patients undergoing FDG-PET/CT hospitalized in our hospital between 2006 and 2013 were studied. Eight RPC cases examined by PET reported in the literature were also assessed. Data from 13 patients total were analyzed. Results: Typical FDG accumulation was noted in tracheobronchial trees of 9 patients, costal cartilage of 5, joints of 5, larynx of 4, nasal cavity/paranasal sinuses of 3, auricles of 3, lymph nodes of 3, and the aorta of 1. One patient showed nasal chondritis on PET scan despite absence of nasal changes on physical examination. Of 5 patients with costochondritis, 4 remained asymptomatic. Of 9 patients with airway FDG accumulation, 8 developed respiratory symptoms and all had CT abnormalities. In the other patient, airway FDG accumulation was evident despite the absence of airway symptoms and a lack of abnormalities in the respiratory function test and CT. PET also revealed bronchial chondritis in asymptomatic patients.In 5 patients with PET post-treatment, FDG accumulation had diminished with symptomatic and inflammatory improvement. Conclusions: FDG-PET/CT is a potentially powerful tool for the early diagnosis of RPC, especially in patients without easily biopsied organ involvement. This modality also facilitates the evaluation of extent of disease and disease activity during treatment. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1039